Evaluation of Solid Waste Management Policy and Implementation in Lagos State: A Case Study of Agege Local Government Area - Ogundele E. O.; Gbadebo S. O. (Darul Yasin Al Sys, 2025)
This study investigates the effectiveness of solid waste management policies and their implementation in the Agege Local Government Area of Lagos State, Nigeria. Utilizing both primary and secondary data sources, the research employs descriptive statistics and analysis of variance (ANOVA) to evaluate respondents' socio-economic characteristics, levels of community satisfaction, and the predictive capacity of existing waste management policies. The demographic findings reveal that the majority of respondents are aged between 41 and 60, with a gender imbalance favoring males (60.3%). An unemployment rate of 17.9% highlights the need for targeted employment strategies within the area. A strong positive correlation (0.929) was found between the effectiveness of waste collection services and community satisfaction, indicating that improved collection significantly enhances public contentment. Key influencing factors include the professionalism of waste collectors and the level of public awareness regarding proper waste practices. The predictive model yields a moderate correlation (R = 0.413) and an R² value of 0.171, suggesting that 17.1% of the variation in policy implementation effectiveness can be explained by the studied variables. The study concludes that sustainable waste management in Agege requires comprehensive policy reform, increased public engagement, and improved service delivery. These measures are essential for enhancing environmental quality and public health across Lagos State.